(untitled) (Research, Society and Development, 2022)
The quality of education is influenced by multiple factors and different authors point out that the teacher’s didactic performance is the determining reason for the quality of student learning. It’s not the only factor, but it’s the most important. Therefore, public policies aimed at the qualification of teacher training are necessary, especially in the case of Brazil, which is in a difficult situation in relation to quality indicators in the teaching and learning processes. The new guidelines for training follow this scenario, in order to induce substantial changes in undergraduate courses. Methodologically, we analyzed the document, from a qualitative approach, by pointing out some limitations and suggesting alternative possibilities. Our objective was to critically reflect on the process of teacher (self) training promoted in undergraduate courses in Brazil. We conclude, for the time being, and considering that much needs to be done in teacher training courses, that the changes are dependent/autonomous of the broad context in which the institutions, courses, curricular components, effective teachers, students and civil servants are inserted. general. To make significant changes possible, all these agents will need to recognize the need to change and assume the task as their own, giving it meaning. That’s process. Analyzing and critically reflecting on the proposed new guidelines can contribute to it.